Prioritizing the Risk Factors of Severe Early Childhood Caries - Noha Samir Kabil; Sherif Eltawil (Dentistry Journal, 2017)
Severe early childhood caries remains the most common chronic disease affecting children. The multifactorial etiology of caries has established a controversy about which risk factors were more significant to its development. Therefore, our study aimed through meticulous statistical analysis to arrange the “well agreed upon” common risk factors in order of significance, to aid the clinician in tailoring an adequate preventive program. The study prioritized or reshuffled the risk factors contributing to severe early childhood caries and placed them in the order of their significance as follows: snacking of sugary food several times a day, increased number of siblings to three or more, night feeding, child self-employed brushing, mother’s caries experience, two siblings, on demand feeding, once/day sugary food, sharing utensils, one sibling, male gender, father’s education, late first dental visit, brushing time, mother’s education, no dental visit, decreased brushing frequency, and no night brushing.